A comparison of physicians’ and other health care professionals’ perceived adoptions of smartphone - Park, Yangil; Putzer, Gavin J. (IJRDO - Journal of Business Management, 2016)
Portable devices such as the smartphone are transforming the healthcare industry. Ourstudy explores the adoption behavior of health professionals in regional hospitals. Thisstudy employed a comparative design via questionnaire to investigate perceptiondifferences among 323 practitioners in US. Professionals were divided into four groups:physician, nurse, administrator, other professional. The results showed significantdifferences in several variables: attitude toward using a smartphone, observability,compatibility, personal demographics, and internal/ external environments. Adoptionrates in large hospital settings approximated 70%; whereas, in smaller settings only 35%.The smartphone adoption in rural areas was less than metropolitan areas; yet, theadvantages of using a smartphone for clinical tasks were well perceived. It appears auser’s perception is significantly different between the groups.